WEBSITE SISTEM PEMESANAN JASA FOTOGRAFI BERBASIS WEB PADA BUNGLON FOTOGRAFI: Application;Photography;Internet;Mysql;Web. - Nurjani, Yeni; Kurnia Dewi, Rizki Moriana (LP2M Universitas Nurdin Hamzah, 2022)
Information technology and the internet are currently experiencing very rapid development along with the growing human needs. One application that uses the internet is a website, with website mediation, communication and information can be presented quickly and precisely. With the availability of the internet that can be accessed by everyone, business entities that want to be widely known by the public need to create a website. Bunglon Photography is a business entity that is engaged in providing photo and video shooting services. Bunglon Photography requires an information system that can expand the dissemination of information about its photography services. Making this application is done by collecting data, system analysis, system and database design, system implementation and system testing. The program is made web-based using the wampserver server and MySQL database.